The intraoperative use of a calliper predicts leg length and offset after total hip arthroplasty. Component subsidence influences the leg length - Maliha Fansur; Nagib A. Yurdi; Reinhard Stoewe (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The purpose of total hip arthroplasty (THA) post-surgery and proper physiotherapy is positive recovery for the patient. Consideration is given to hip replacement biomechanics by ensuring no discrepancies in limb length (LL) and a stable prosthesis. Therefore, the patient must have proper preoperative planning and communication and a clear understanding of what to expect. Methods A prospective series of 59 THA operated by a single surgeon via Hardinge approach was studied, using an intraoperative calliper (CAL) to predict the change of LL and offset. We compared the results of the intraoperative changes before and after THA implantation with the reference of these values on anteroposterior x-ray pelvis. The importance of leg length balance and a good offset restoration is questioned, and the effect of component subsidence on leg length is considered. Results The average preoperative leg length discrepancy was −6.0 mm, postoperatively +3.6 mm. There was a strong correlation between the CAL measurements and the values on the x-ray (LL, r=0.873, p<0.01; offset, r=0.542, p<0.01). Reliability is better for limb length than for offset. These results are comparable within the literature and the statistical results from other studies reviewed. In addition, we evaluate the importance of subsidence of the prosthesis components for long-term results. Conclusion The intraoperative use of CAL gives excellent results in predicting the final LL and offset after THA. Considering subsidence of prosthesis components, a target zone around +5 mm might be more suitable for leg length directly postoperatively. Moreover, surgeons must discuss the topic of leg length discrepancy (LLD) intensively with the patient pre-operatively. Level of evidence Level 4, prospective cohort study